2015
DOI: 10.4014/jmb.1410.10014
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Community and Its Assembly Associated with Age and Diet in Chinese Centenarians

Abstract: Increasing evidence suggests that gut microbiota underpin the development of health and longevity. However, our understanding of what influences the composition of this community of the longevous has not been adequately described. Therefore, illumina sequencing analysis was performed on the gut microbiota of centenarians (aged 100-108 years; RC) and younger elderlies (aged 85-99 years; RE) living in Bama County, Guangxi, China and the elderlies (aged 80-92 years; CE) living in Nanning City, Guangxi, China. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
113
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(136 citation statements)
references
References 40 publications
18
113
2
3
Order By: Relevance
“…Here, we used this advanced sequencing technology based on the 16S rRNA sequences in microbial genomes to analyze the gut microbiota in 31 acne patients using 31 paired healthy individuals as the controls. In healthy controls, the commonest phylum was Bacteroidetes, followed by Firmicutes and Proteobacteria, consistent with other studies from Chinese fecal samples 15,17 but different from the results from Americans and Egyptians, in which the commonest phyla were Firmicutes and then Bacteroidetes. 14 The major taxa are related to human colon environment, and the ingredients of diets in different countries may affect the structure of gut microbiota.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Here, we used this advanced sequencing technology based on the 16S rRNA sequences in microbial genomes to analyze the gut microbiota in 31 acne patients using 31 paired healthy individuals as the controls. In healthy controls, the commonest phylum was Bacteroidetes, followed by Firmicutes and Proteobacteria, consistent with other studies from Chinese fecal samples 15,17 but different from the results from Americans and Egyptians, in which the commonest phyla were Firmicutes and then Bacteroidetes. 14 The major taxa are related to human colon environment, and the ingredients of diets in different countries may affect the structure of gut microbiota.…”
Section: Discussionsupporting
confidence: 81%
“…In healthy controls, the commonest phylum was Bacteroidetes, followed by Firmicutes and Proteobacteria, consistent with other studies from Chinese fecal samples but different from the results from Americans and Egyptians, in which the commonest phyla were Firmicutes and then Bacteroidetes . The major taxa are related to human colon environment, and the ingredients of diets in different countries may affect the structure of gut microbiota .…”
Section: Discussionsupporting
confidence: 78%
“…The dietary information of the crewmembers was monitored using a food frequency questionnaire (FFQ) before and after 105d‐E (Wang et al ., ). Survey content was divided into 23 kinds of food and food combinations, the food intake ( M ) was calculated as follows: M=μi×min …”
Section: Methodsmentioning
confidence: 97%
“…Importantly, the mucin-degrading bacterium Akkermansia muciniphila was shown to reverse these metabolic disorders by strengthening the intestinal barrier [589]. In our study old conventional mice had lower abundance of Akkermansia, which has also been reported previously both in humans and mice [590,591]. Akkermansia was also less abundant after transfer of old microbiota to germ-free mice at early time points.…”
Section: Discussionsupporting
confidence: 87%